The politics of outer space: colonisers and missionaries in Russian fantasy film of the 1930s. (4th May 2017) - Sputnitskaia, Nina
Abstract: The theme of the colonisation of other planets in Soviet cinema of the 1930s has so far not received enough attention in film studies, because the fantasy genre was not a major trend in the cinema of that period. Nevertheless, it is important to draw attention to the fact that, against the background of the country's isolation, within it an interest in the theme of outer space developed and came to fruition among film-makers. Research in the field of fantasy films of the 1930s is coupled here with scientific developments in aeronautics: to a certain extent the films bring these discoveries to the screen, but on the whole film-makers courageously predict the future of Soviet man as conqueror of the depths of outer space. Attempts to develop the theme are realised in the genre of utopia (a narrative about the distant future) in the time of the victory of World Communism, and in the genre of defence sci-fi. The focus of attention in this article is on the aesthetic criteria of the fantasy film and the evolution of the mission of Soviet pilots in the conquest of 'virgin lands'.